Rhodium(III)-Catalyzed Asymmetric Borylative Cyclization of Cyclohexadienone-Containing 1,6-Dienes: An Experimental and DFT Study - Tan, Yun-Xuan; Zhang, Fang; Xie, Pei-Pei; Zhang, Shuo-Qing; Wang, Yi-Fan; Li, Qing-Hua; Tian, Ping; Hong, Xin; Lin, Guo-Qiang (Journal of the American Chemical Society, 2019)
Because of the inherent difficulty in differentiating two olefins, the development of metal-catalyzed asymmetric cyclization of 1,6-dienes remains challenging. Herein, we describe the first rhodium(III)-catalyzed asymmetric borylative cyclization of cyclohexadienone-tethered mono-, 1,1-di-, and (E)-1,2-disubstituted alkenes (1,6-dienes), affording optically pure cis-bicyclic skeletons bearing three or four contiguous stereocenters with high yields (25–93%), and excellent diastereoselectivities (>20:1 dr) and enantioselectivities (90–99% ee). This mild catalytic approach is generally compatible with a wide range of functional groups, which allows several facile conversions of the cyclization products. Furthermore, on the basis of our SAESI-MS experiment and computational study, a Rh(I)/(III) catalytic cycle is proposed in this tandem reaction, and the Rh(I) active species catalyzes the overall transformation via sequential oxidative addition of B2pin2, olefin insertion, cyclizing conjugate addition, and reductive elimination. The irreversible conjugate addition determines the overall regioselectivity of borylative cyclization, and the ring strain favors the formation of 5,6-bicyclic structure. This highlights the control of ring strain in diene cyclizations, which provides a useful basis for future reaction designs.